The Perception of Fluency in Native and Nonnative Speech. Issue 3 (September 2014) - Bosker, Hans Rutger; Quené, Hugo; Sanders, Ted; de Jong, Nivja H.
<x xml:space="preserve">Abstract</x> Where native speakers supposedly are fluent by default, nonnative speakers often have to strive hard to achieve a nativelike fluency level. However, disfluencies (such as pauses, fillers, repairs, etc.) occur in both native and nonnative speech and it is as yet unclear how fluency raters weigh the fluency characteristics of native and nonnative speech. Two rating experiments compared the way raters assess the fluency of native and nonnative speech. The fluency characteristics were controlled by using phonetic manipulations in pause (Experiment 1) and speed characteristics (Experiment 2). The results show that the ratings of manipulated native and nonnative speech were affected in a similar fashion. This suggests that there is no difference in the way listeners weigh the fluency characteristics of native and nonnative speakers.